Implementation of Project-Based Learning (PjBL) Model Assisted by Interactive Digital Media in IPAS Learning for Grade IV Elementary School : Sistematic Literature Review - Rahmawati, Galih; Atmojo, Idam Ragil Widianto; Chumdari, Chumdari (Social, Humanities, and Educational Studies (SHES): Conference Series, 2026)
This study was motivated by the importance of innovative learning models that are relevant to technological developments and the characteristics of elementary school students in the digital era. Science and Social Studies (IPAS) learning requires an approach that is contextual, meaningful, and able to actively involve students in the learning process. One of the appropriate models is Project Based Learning (PjBL), especially when integrated with interactive digital media. This study aimed to analyze and synthesize research findings related to the implementation of the PjBL model assisted by interactive digital media in Grade IV elementary school IPAS learning. The method used was a Systematic Literature Review (SLR) with the PRISMA approach. Data sources were obtained from the PoPCites database through stages of identification, screening, eligibility, and inclusion. From the initial 100 articles, 20 relevant articles met the inclusion criteria and were analyzed comprehensively. The results showed that the implementation of PjBL assisted by interactive digital media such as Canva, Padlet, Wordwall, Genially, YouTube, and Augmented Reality was able to improve student motivation, learning participation, conceptual understanding, critical thinking skills, creativity, collaboration, and learning outcomes in IPAS subjects. Interactive digital media also helped transform abstract IPAS concepts into more concrete, visual, and meaningful learning experiences. Therefore, the PjBL model assisted by interactive digital media is considered an effective and adaptive learning strategy to support the implementation of the Merdeka Curriculum and the development of 21st-century competencies in elementary schools.